Optimization of respiratory-gated auricular vagus afferent nerve stimulation for the modulation of blood pressure in hypertension - Garcia, Ronald G.; Staley, Rachel; Aroner, Sarah; Stowell, Jessica; Sclocco, Roberta; Napadow, Vitaly; Barbieri, Riccardo; Goldstein, Jill M. (Frontiers in Neuroscience, 2022)
Background The objective of this pilot study was to identify frequency-dependent effects of respiratory-gated auricular vagus afferent nerve stimulation (RAVANS) on the regulation of blood pressure and heart rate variability in hypertensive subjects and examine potential differential effects by sex/gender or race. Methods Twenty hypertensive subjects (54.55 ± 6.23 years of age; 12 females and 8 males) were included in a within-person experimental design and underwent five stimulation sessions where they received RAVANS at different frequencies (i.e., 2 Hz, 10 Hz, 25 Hz, 100 Hz, or sham stimulation) in a randomized order. EKG and continuous blood pressure signals were collected during a 10-min baseline, 30-min stimulation, and 10-min post-stimulation periods. Generalized estimating equations (GEE) adjusted for baseline measures were used to evaluate frequency-dependent effects of RAVANS on heart rate, high frequency power, and blood pressure measures, including analyses stratified by sex and race. Results Administration of RAVANS at 100 Hz had significant overall effects on the reduction of heart rate (β = −2.03, p = 0.002). It was also associated with a significant reduction of diastolic (β = −1.90, p = 0.01) and mean arterial blood pressure (β = −2.23, p = 0.002) in Black hypertensive participants and heart rate in female subjects (β = −2.83, p = 0.01) during the post-stimulation period when compared to sham. Conclusion Respiratory-gated auricular vagus afferent nerve stimulation exhibits frequency-dependent rapid effects on the modulation of heart rate and blood pressure in hypertensive patients that may further differ by race and sex. Our findings highlight the need for the development of optimized stimulation protocols that achieve the greatest effects on the modulation of physiological and clinical outcomes in this population.